Feasibility and Acceptability of a Compressed Caregiver Training Program to Treat Child Behavior Problems. Issue 3 (May 2023) - Edelstein, Matthew L.; Sullivan, Alicia; Becraft, Jessica L.
In an effort to address some of the criticisms of Behavioral Parent Training programs (BPT; high attrition, reliance on caregiver report measures), the current study examined the feasibility, acceptability, and outcome of an intensive behavior treatment program (120-minute sessions for 5 days/week over the course of 2 weeks). Using a changing criterion single case experimental design, 12 children ( M child age = 4.9 years) and their primary caregivers completed the 2-week function-based intervention procedure designed to increase children's frustration tolerance via a wait training procedure based on the principles of applied behavior analysis. Using both direct observation and standardized measures, results indicated that the treatment was effective in reducing childhood behavior problems, both within and between appointments (Cohen's d s = 3.2 and 1.37, respectively). Preliminary evidence suggests that a compressed treatment package designed to train caregivers in function-based intervention strategies is feasible and acceptable.